Safety and Immunogenicity of ChAd63/MVA Pfs25-IMX313 in a Phase I First-in-Human Trial - de Graaf, Hans; Payne, Ruth O.; Taylor, Iona; Miura, Kazutoyo; Long, Carol A.; Elias, Sean C.; Zaric, Marija; Minassian, Angela M.; Silk, Sarah E.; Li, Lee; Poulton, Ian D.; Baker, Megan; et al. (Frontiers in Immunology, 2021)
BACKGROUND: Transmission blocking vaccines targeting the sexual-stages of the malaria parasite could play a major role to achieve elimination and eradication of malaria. The Plasmodium falciparum Pfs25 protein (Pfs25) is the most clinically advanced candidate sexual-stage antigen. IMX313, a complement inhibitor C4b-binding protein that forms heptamers with the antigen fused to it, improve antibody responses. This is the first time that viral vectors have been used to induce antibodies in humans against an antigen that is expressed only in the mosquito vector. METHODS: Clinical trial looking at safety and immunogenicity of two recombinant viral vectored vaccines encoding Pfs25-IMX313 in healthy malaria-naive adults. Replication-deficient chimpanzee adenovirus serotype 63 (ChAd63) and the attenuated orthopoxvirus modified vaccinia virus Ankara (MVA), encoding Pfs25-IMX313, were delivered by the intramuscular route in a heterologous prime-boost regimen using an 8-week interval. Safety data and samples for immunogenicity assays were taken at various time-points. RESULTS: The reactogenicity of the vaccines was similar to that seen in previous trials using the same viral vectors encoding other antigens. The vaccines were immunogenic and induced both antibody and T cell responses against Pfs25, but significant transmission reducing activity (TRA) was not observed in most volunteers by standard membrane feeding assay. CONCLUSION: Both vaccines were well tolerated and demonstrated a favorable safety profile in malaria-naive adults. However, the transmission reducing activity of the antibodies generated were weak, suggesting the need for an alternative vaccine formulation.